BATAK TOBA SOCIETY'S PERCEPTIONS ABOUT SEX EDUCATION FOR ADOLESCENTS IN THE PARPAREAN III NEIGHBORHOOD PARPAREAN III VILLAGE PORSEA DISTRICT TOBA REGENCY IN 2023 - Munarni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Sex education is a clear and correct information regarding the issue of human sexuality, which includes the occurrence of conception, pregnancy, sexual behavior, sexual relations and health, psychological and social aspects. The issue of sexual education provided should be related to the norms prevailing in society, what is prohibited, what is legal and how to do it without violating the rules that apply in society. This study aims to determine the perception of the Batak Toba community about sex education for adolescents in the Parparean III environment, Parparean III Village. This research is descriptive using primary data obtained through a questionnaire. The sample in this study was the Batak Toba people who had teenagers who were obtained using a total sampling technique. From the results of this study obtained data, respondents who have positive perceptions as many as 43 people (81.1%) and negative 10 people (18.9%). Given the importance of sex education for adolescents, it is necessary to coordinate between the government, health workers and the community to unifying perceptions about sex education so that adolescents get clear and correct information about sexuality to improve their reproductive health.